2020
DOI: 10.4081/jphr.2020.1883
|View full text |Cite
|
Sign up to set email alerts
|

The Fight against Stigma: Multilevel Stigma Interventions in Schizophrenia Patients

Abstract: Background: Stigma is one of the main factors causing pasung (physical restraint or confinement in Indonesian terms) in schizophrenia patients. It is the main obstacle to reducing the number of pasung throughout the world. Thus, there is a need for appropriate interventions to reduce stigma in schizophrenia patients who go through pasung. This study aims to identify multilevel stigma interventions in people with schizophrenia who go through pasung (physical restraint and confinement). It can be applied and ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
(15 reference statements)
2
3
0
9
Order By: Relevance
“…This finding further reinforces previous findings which reported that there is a relationship between knowledge and people's attitudes towards people with mental disorders in the Colomadu 1 Health Center Work Area with a significance value (p-value) of 0.000 [24]. This is also in line with the research of [25]. who reported that there was a relationship between the level of education and the level of knowledge about mental health with people's attitudes towards mental patients in RW XX Duwet Village.…”
Section: Knowledgesupporting
confidence: 92%
See 1 more Smart Citation
“…This finding further reinforces previous findings which reported that there is a relationship between knowledge and people's attitudes towards people with mental disorders in the Colomadu 1 Health Center Work Area with a significance value (p-value) of 0.000 [24]. This is also in line with the research of [25]. who reported that there was a relationship between the level of education and the level of knowledge about mental health with people's attitudes towards mental patients in RW XX Duwet Village.…”
Section: Knowledgesupporting
confidence: 92%
“…In line with research conducted by [25]by obtaining a significant value of 0.000, it means that there is a relationship between the level of education and people's attitudes towards patients with mental disorders. Research conducted by Wiharjo (2014) also states that there are other factors that influence attitudes, namely community stigma, with the result (p) = 0.000 (p <0.05), meaning that there is a significant positive relationship between community stigma and people's attitudes towards people with schizophrenia .…”
Section: Attitudesupporting
confidence: 73%
“…"chiflados", "brotes"; "manicomios", "ataques", "dementes"; "encierro", así como también se expone a la esquizofrenia erróneamente en material audiovisual como series, películas o cortometrajes, alimentando la presencia de estereotipos asociados a la peligrosidad o violencia mediante los cuales se liga directamente a la esquizofrenia con actos delictivos (4,5,7,8,9,10,11,12,13,14,15,17,19,21,22,23,24).…”
Section: Discussionunclassified
“…atención psiquiátrica eran ubicados en lugares lejanos a la comunidad, por lo que se perpetuaban las creencias de peligrosidad, incurabilidad, rechazo e imposibilidad de inserción en la sociedad de las personas con diagnóstico de esquizofrenia, quienes eran percibidos como "anormales", "desadaptados", incapaces de aportar de manera positiva a la sociedad, por lo que su inclusión fue limitada o inalcanzable. Dichas acciones se siguen repitiendo en la actualidad, donde la inclusión de personas con esquizofrenia dentro de la sociedad es muy deficiente aún con el paso del tiempo (4,5,7,8,9,10,11,12,13,14,15,17,19,21,22,23,24).…”
Section: Artículo Originalunclassified
“…The most important thing is the need for stigma prevention adapted to certain ethnic backgrounds in increasing knowledge about mental health. Meanwhile, other studies have found that multilevel stigma interventions can reduce stigma levels in schizophrenics who undergo shackling (Bachtiar et al, 2020)…”
Section: Discussionmentioning
confidence: 99%